Historical-pedagogical analysis of model and simulation development as a part of tactical training of military professionals - KOS, Mykola (Journal of Education, Technology and Computer Science, 2013)
We have provided a short description of development of models and simulationof tactical and strategic actions in training of military professional. We believethat better and more rigorous research of development and new trends ofmodels and simulation is needed in order to gain the necessary knowledge onhow to use their experience in development of perspective systems of modelsand simulation of combat actions for Ukrainian Armed Forces. This is especiallytrue for the training of future officers in Military Higher Education Institutions.A further line of research may be the analysis of development of nationalmodels and simulation of various actions in military sphere, particularly in systemof military education.